Orofacial Manifestations Associated with Muscular Dystrophies: A Review - Petros Papaefthymiou; Kyriaki Kekou; Fulya Özdemir (Galenos Yayinevi, 2022)
The aim of this review is to evaluate the developmental, functional, and morphological aspects of the craniofacial complex in patients with myotonic dystrophy type 1 (DM1), Facioscapulohumeral muscular dystrophy (FSHD), and Duchenne muscular dystrophy (DMD). The degree of disease onset and severity varied from patient to patient, and most parameters indicated a greater degree of deterioration in older patients. It was found that all the muscular dystrophies studied showed altered craniofacial morphology, with malocclusion as the most consistent clinical characteristic. Particularly DM1 patients, who are the most studied, showed significant vertical aberration and post-normal occlusion. DMD patients are reported mainly with altered dental arch dimensions which influence functional capacities. Data for FSHD patients are very limited, but facial asymmetry and muscular weakness appear to be the most prominent findings. Patients with muscular dystrophies present deviations in growth and development as well as in orofacial morphology. Increased prevalence of malocclusions, of both skeletal and dental origins, characterize patients with muscular dystrophies. Different dentofacial characteristics are reported among patients with different types of muscular dystrophies. Further research is needed to clarify the orofacial phenotypic expression of muscular dystrophies.